Afterlife Beliefs, Life Extension and Gender: Evidence for Life Extension Technologies Reduces Death Thought Accessibility Among Males - Uri Lifshin; Jeff Greenberg; Melissa Soenke; Peter J. Helm; Tom Pyszczynski (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study investigates whether reading about Indefinite Life Extension (ILE) can reduce death thought accessibility, particularly among men, as a way to manage death-related concerns. The study aims to explore gender differences in the psychological function of ILE as a terror management strategy. Methodology: An experimental design was used, involving 110 American undergraduate students. Participants were randomly assigned to read about ILE, the afterlife, or a neutral technological advance (teleportation) following a mortality salience prime. The primary outcome measured was death thought accessibility (DTA), with gender as a key variable. Findings: The results revealed that, after being reminded of mortality, reading about the possibility of ILE significantly reduced DTA among men compared to the control condition. However, this effect was not observed among women, who did not show a similar reduction in DTA after reading about ILE. Research Implications: These findings contribute to the growing literature on the terror management function of ILE, highlighting the role of gender in moderating responses to death-related concerns. The study suggests that ILE may serve as an effective strategy for men in managing existential anxiety, whereas women may rely more on traditional beliefs in the afterlife. Originality/Value: This study offers new insights into the gender-specific psychological mechanisms underlying the appeal of life extension technologies, expanding the understanding of how different groups use ILE as a tool for managing death anxiety.